The Influence of Social Structure and Behavior and Investment on Poverty in East Kalimantan Province - Gregorius, Gerry; Suharto, Rahcmad Budi; Jiuhardi, Jiuhardi; Setyadi, Djoko (International Journal of Economics (IJEC), 2025)
This study aims to analyze and test the influence of 1) Community Structure on Community Behavior and Poverty; 2) Community Behavior and Investment on Poverty; 3) Investment on Community Welfare and 4) Welfare on Poverty in East Kalimantan Province. This study uses a descriptive quantitative approach with panel data of nine (9) districts/cities in East Kalimantan in 2011-2023. The data used are population density, open unemployment rate, Domestic Investment, Foreign Investment, length of schooling, expected length of schooling, PMDN, PMA, life expectancy data, average length of schooling, gross regional domestic product, human development index, percentage of poor population, depth of poverty and severity of poverty in East Kalimantan. Data analysis used SEM ( Structural Equation Modeling ) analysis using WarPLS 8.0 software. The results of the study indicate that population structure has a positive and significant effect on community behavior and a negative and significant effect on poverty. Community behavior has a negative and significant effect on poverty, in contrast to insignificant investment, investment has a positive and significant effect on welfare directly and welfare has a negative and significant effect on poverty.